Occurrence and molecular identification of zoonotic microsporidia in pet budgerigars (Melopsittacus undulatus) in Turkey. (17th October 2020) - Pekmezci, Didem; Yetismis, Gamze; Esin, Cagatay; Duzlu, Onder; Colak, Zeynep Nurselin; Inci, Abdullah; Pekmezci, Gokmen Zafer; Yildirim, Alparslan
Abstract: Encephalitozoon spp. and Enterocytozoon bieneusi are well-known microsporidian pathogens, recently classified as fungi, infecting humans and reptiles, mammals, and birds. Budgerigars ( Melopsittacus undulates ) are the most preferred captive pet birds in the households. Prevalence and molecular data on microsporidian species in budgerigars are scarce worldwide. The aim of the present study was to investigate the occurrence and genotypes of Encephalitozoon spp. and E. bieneusi in budgerigars, and to reveal their zoonotic potential. A total of 143 fecal samples were collected from owned healthy budgerigars in Turkey. Encephalitozoon spp. and E. bieneusi were examined by nested PCR targeting the ribosomal internal transcribed spacer (ITS) region and sequenced for identifying Encephalitozoon spp. and E. bieneusi. The overall prevalence of E. hellem and E. bieneusi was 14.7% (21/143) and 3.5% (5/143), respectively. Two genotypes of E. hellem were identified, including one known 1A ( n  = 18) and a novel TURK1B ( n  = 3). In addition, we determined two E. bieneusi genotypes, including one known N ( n  = 2) and a novel TURKM1 ( n  = 3). E. hellem 1A and novel TURK1B clustered as a sister taxon, and genotype N and novel TURKM1 genotypes fall into group 2 of E. bieneusi in the phylogenetic tree. Novel genotypes of E. hellem and E. bieneusi were described for the first time in the avian host. Moreover, E. bieneusi genotype N was first detected in avian hosts in the present study. This study contributes to the current knowledge on the molecular epidemiology and transmission dynamics of E. hellem and E. bieneusi . Lay Summary: Spore producing microsporidia are ubiquitous, obligate, and intracellular fungus defined as emerging opportunistic pathogens of humans, livestock, companion animals, wild mammals, birds, and water worldwide. The occurrence of microsporidia in animals could be risky for human public health.